Application of Data Mining for Slot Time Prediction at International Airports in Indonesia: J48 Algorithm - Renddy Wandhana Suryaman; Gunawan Wang; Viany Utami Tjhin (Aptisi Transactions On Technopreneurship (ATT), 2022)
Abstract In aviation, the safety and smooth flow of flight traffic is a business core, where every flight traffic service is expected to avoid delays caused by aircraft movement either in the air or on land. Therefore, the time slot at the airport is essential for the accuracy of the movement of aircraft, both Departure and Arrival, and this is intended to avoid delays caused by the accumulation of queues of planes that will depart and planes that will land, with a large number of aircraft movements at the International Airport. Soekarno Hatta requires analysis with data mining techniques such as the J48 algorithm and Decision Tree, and Naïve Bayes.